Formation of porous silicon: mechanism of macropores formation in n-type si - Nurul Izni Rusli,; Mastura Shafinaz Zainal Abidin,; Budi Astuti,; Nihad K. Ali, (Universiti Kebangsaan Malaysia, 2013)
We report the formation of macropores in n-Si (100) substrates for different etching times of 20, 40 and 60 min at a constant current density of 25 mA/cm2 under front-side illumination in HF:ethanol (1:4) solution. After etching for 20 min, four-branch-shaped pores of various sizes were observed at discrete locations. Etching time of 40 min led to the formation of highly connected four-branch-shaped pores as the branches of adjacent pores appeared to connect to each other. As the etching time was increased further to 60 min, the density of interconnected branches increased remarkably. The macropore formation process occurred in three consecutive phases. The current burst model was used to discuss this process. Formation of four-branch-shaped pores at random locations were observed because current bursts are more likely to nucleate where other current bursts took place initially.